EFFECT OF PLANT GROWTH REGULATORS ON GROWTH, YIELD AND EXPORTABLE QUALITY OF CUT ROSES - S. MUTHU KUMAR; V. PONNUSWAMI; M. JAWAHARLAL; A. RAMESH KUMAR (The Bioscan, 2012)
An experiment was conducted to study the influence of various growth regulating chemicals on growth, yield and quality characters of cut rose cv. First Red. The study involved pre harvest spraying with gibberellic acid (50, 100ppm), maleic hydrazide (50, 100ppm) and salicylic acid (25, 50ppm). Gibberellic acid at higher concentra- tion of 100ppm as a preharvest spray excerted a significant influence on crop growth and recorded highest mean values for plant height (76.18cm), stalk length (60.98cm), stem girth (1.66cm) and total chlorophyll content (1.826mg g-1). Similarly the application of gibberellic acid at 100 ppm level drastically increased the quality traits viz., mean flower diameter (6.89cm), anthocyanin content (0.1970 OD value) and vase life (2.6 days). Likewise the earliest flowering (40.00 days) was also obtained from preharvest spray of gibberellic acid at 100 ppm. The preharvest application of maleic hydrazide at 100 ppm resulted in the maximum mean number of branches per plant (4.47) and number of flower per plant (16.50).